Transfer Antarbank Menggunakan Aplikasi Flip dalam Perspektif Fikih Muamalah - Nuraisyah Nuraisyah; Muhammad Kasim; Muhammad Harsya Bachtiar (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2023)
This study aims to determine the practice and law of using the Flip application in the perspective of muamalah fiqh. The problems that the authors raise in this study are: First, how is the practice of using the Flip application in the transfer process to other banks. Second, how is the law on interbank transfers using the Flip application from a muamalah fiqh perspective. The research method used in this research is library research with a normative approach. The data used in this study came from primary and secondary data in the form of books, books, journals, articles and scientific literature related to the title of this study. The results of this study conclude that: 1) The practice used to transfer funds in the Flip application is that users only need to follow the transaction procedure they want to make by filling in the transfer request data, transferring funds in the nominal amount they want to send plus a unique code to the same Flip bank account with the user's bank, then send proof of transfer of funds via the Flip application and the user's e-mail. 2) Based on muamalah fiqh analysis, interbank fund transfer transactions through the Flip application are allowed because the transactions carried out avoid usury and garar and there are benefits to ease fund transfer transactions between different banks.